KANDUNGAN TIMBAL DAN KADMIUM PADA CACING NIPAH (Namalycastis rhodochorde) DAN SEDIMEN PERAIRAN PANTAI INDRAGIRI HILIR - Sugeng Abriyanto; Syafruddin Nasution; Sofia Anita (Jurnal Ilmu Lingkungan, 2016)
This research was conducted at Kuala Enok coastal water of Indragiri Hilir District. Samples of sediment and nypha palm worm N. rhodochorde have been taken from six locations of two villages those were Kuala Enok and Tanah Merah coastal water. Analysis of metal concentrations both in sediment and nypha palm worm conducted by using Atomic Absorption Spectrophotometer (AAS) Shimadzu A7000. The result showed that concentration of Plumbum (Pb) and Cadmium (Cd) in sediment which were between 74.44 10-2 – 108.64 10-2 ppm (Pb) and 0.55 10-2 – 0.96 10-2 ppm (Cd). While the concentration of these metals in nypha palm worm N. rhodochorde which were between 19,26 10-2 – 46.57 10-2 ppm (Pb) and 0.20 10-2 – 0.51 10-2 (Cd), indicating that the concentration in both sediment and nypha palm worm revealed the positive correlation.